Association between coffee and caffeine intake and functional dyspepsia - Glareh Koochakpoor; Asma Salari-Moghaddam; Ammar Hassanzadeh Keshteli; Ahmad Esmaillzadeh; Peyman Adibi (Scientific Reports)
Abstract No previous study has examined the association between coffee and caffeine intake and odds of functional dyspepsia (FD). The aim of this study was to investigate the association between coffee and caffeine intake and odds of FD and its components in a large sample of Iranian adults. In this cross-sectional study on 3362 adults aged 18–55 years, a validated food frequency questionnaire (DS-FFQ) was used to assess dietary intakes. A validated modified Persian version of the Rome III questionnaire was used for assessment of FD. Logistic regression was applied to compute odds ratios for FD and its components considering a wide range of covariates. Mean age of study population was 36.2 ± 7.8 years, of them 58.3% were females. The prevalence of FD among study participants was 14.5%. The prevalence of post-prandial fullness, early satiation, and epigastric pain was 7.6, 5.8, and 7.6%, respectively. After controlling for potential confounders, no significant association was observed between coffee (OR: 1.27; 95% CI: 0.86–1.87), and caffeine (OR: 1.00; 95% CI: 0.99–1.02) consumption and odds of FD. In addition, coffee and caffeine consumption was not significantly associated with odds of FD symptoms such as early satiation, post-prandial fullness, and epigastric pain. This was also the case when the analysis was done stratified by gender and BMI status. In conclusion, we found no significant association between coffee and caffeine consumption with odds of FD and its symptoms. Further research in other populations with high coffee consumption is needed.